EXAMINING THE ENDOGENEITY OF ESG PRACTICE AND FIRM PERFORMANCE OF SPORT-RELATED ENTERPRISES: THE MODERATING EFFECT OF R&D INTENSITY - Chin Yi Fang, (PEOPLE: International Journal of Social Sciences, 2025)
The number of sports-related enterprises has increased; however, there is little research on the factors influencing the performance of these enterprises and the sustainability of their companies. Enterprises have expanded their focus from pursuing financial returns to embracing social responsibility and sustainable development, marking a transition from corporate social responsibility to Environmental, Social, and Governance (ESG). Hence, the objectives of this paper are (1) establishing an efficiency index incorporating multiple inputs/outputs for sports-related companies; (2) examining the relationship between ESG practice score and firm performance (FP) including financial performance and corporate efficiency; (3) examining the moderating effect of research and development (R&D) intensity in sports-related companies on ESG and FP. First, this study used the Slacks-based Measure-Data Envelopment Analysis (SBM-DEA) to evaluate the long-term FP in the sports certification and sports manufacturing industries. This study further examines the endogenous and nonlinear relationship between FP and ESG using the second stage least square (2SLS), aiming to measure the turning point score where a U-shaped relationship is present. Meanwhile, this research examines the moderating effect of R&D intensity on ESG and the individual E, S, G scores and FP. The study confirms the presence of endogeneity between ESG scores and FP through the use of 2SLS. The findings show that ESG scores exhibit an inverted U-shaped relationship with ROA, ROE, and efficiency. Specifically, E scores have an inverted U-shaped relationship with ROA, ROE, and efficiency. G scores show an inverted U-shaped relationship with ROA and ROE. Additionally, R&D intensity positively moderates the relationship between ESG scores and ROE. Future research could expand on these findings by utilizing ESG and financial data from other countries to provide a global perspective.